Ecological and Economic Dissonance Debate on Kilimanjaro Region: Reflecting on 2-Basic Questions Case to Establish E1/E2 - Leonard, Msaki Juda; Mwita, Kelvin; Ruoja, Cesilia (American Journal of Trade and Policy, 2015)
Studying an interaction between more than one variable, both in influence and action is never an easy task, but establishing a key functional observation and question is even extremely difficult to an academician. The current literature therefore tries to re-establish an empirical debate between bi-polar ends, taking the influence of human destructive-constructive ends on both variables ecosystem (E1) and economic needs (E2).Kilimanjaro has been taken to represent a case in Tanzania reflecting African 4 – zones on economic agriculture, as it represents among sectors of economy, 47 percent of GDP and employs 85 percent of Tanzanian population. The current literature refers to Global perspective as Global warming covers not only Africa but the whole world reforms platforms.Institutional suggestions therefore cover solutions in terms of theoretical and empirical reflections for both. Where economic parameters and statistical dimensions cover the most dynamic era of plans, actions and the way forward (1990s -2000s). The evils of poverty has been linked to the impacts of unbalanced Dr. Msaki’s ratio (GE1/GE2=ɼ˚), where question A and B articulate further platforms for future researched. The literature concludes by re-establishing an implementation cycle of root I and II focused on balancing criterion of ɼ˚- establishment in terms of culture, strategies, focus and policies.JEL Classifications Code: E6
Keywords: Ecosystem; deforestation; biodiversity; economic aggregates; GFCF; GDP; ecology; GE1; GE2; r˚, O2; population density; par capital; bi-polar